2009
DOI: 10.1158/1078-0432.ccr-09-0111
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Methylation ofAPC, MGMT, RASSF2A, andWif-1Genes in Plasma as a Biomarker for Early Detection of Colorectal Cancer

Abstract: Purpose: To identify epigenetic molecular makers in plasma for the early detection of colorectal cancer. Experimental Design: We retrospectively analyzed the methylation status of 10 genes in fresh-frozen tissues and corresponding plasma samples from 243 patients with stage I and II sporadic colorectal cancer, 276 healthy individuals, and plasma from 64 colorectal adenoma patients using methylation-specific PCR. The methylation score (M score) was used to find molecular markers with high sensitivity and specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
117
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(128 citation statements)
references
References 28 publications
4
117
1
4
Order By: Relevance
“…The reported methylation status of the promoter of APC varies greatly among studies of CRC in different populations (16)(17)(18)(19)(20). Moreover, hypermethylation of the APC promoter has been shown to be relatively common in other gastrointestinal neoplasms, including those of the stomach, liver, pancreas and oesophagus (17,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported methylation status of the promoter of APC varies greatly among studies of CRC in different populations (16)(17)(18)(19)(20). Moreover, hypermethylation of the APC promoter has been shown to be relatively common in other gastrointestinal neoplasms, including those of the stomach, liver, pancreas and oesophagus (17,29).…”
Section: Discussionmentioning
confidence: 99%
“…The APC promoter methylation rate has been detected in CRC and normal colorectal mucosa at a range of 11 to 62% in different populations, and has been suggested to moderate the Wnt signalling pathway (16)(17)(18)(19)(20). Studies have indicated that IGFBP7 is inactivated by DNA methylation in human colon, lung and breast cancer (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…The Wnt signaling pathway is crucial for stem cell survival, proliferation, differentiation, and chemo-/radioresistance (37,38) due to the action of Wnt inhibitory factor 1 (WIF-1), a critical inhibitor of the Wnt signaling pathway (39). Several studies have demonstrated that aberrant activation of the Wnt signaling pathway due to genetic and epigenetic alterations occurs in several types of cancer (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…WIF1 is known to be downregulated in many malignant tumors such as hepatocellular carcinoma, 11,12 nasopharyngeal carcinoma, 13,14 lung cancer, 9,15 colon cancer, 14 renal cell carcinoma, 16 esophageal adenocarcinoma, 17 melanoma, 18 and bladder cancer. 19 The main mechanism of WIF1 inactivation is aberrant promoter methylation, as demonstrated by the inverse correlation between WIF1 promoter methylation and expression of WIF1 mRNA or protein 8,11,12,[19][20][21][22][23][24] and restoration of WIF1 expression by promoter demethylation treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors support the theory that promoter methylation occurs in the early stage of carcinogenesis based on the observation that genes of nonneoplastic tissue from organs containing tumor are more frequently methylated than those of tissue from patients without tumor. 14,17,24 However, studies on the methylation status of nonneoplastic tissue adjacent to tumors of various organs revealed controversial results. It has been reported that WIF1 promoter hypermethylation is more frequent in adjacent normal colorectal mucosa from cancer patients compared with normal mucosa from patients without tumor.…”
Section: Discussionmentioning
confidence: 99%